Displacement Washing of Kraft Pulp at Various Wash Water Temperature - Potůček, František; Rahman, Md. Mostafizur (My University, 2019)
The aim of this paper was to investigate the influence of the wash liquid temperature on the displacement washing efficiency of unbeaten unbleached kraft coniferous pulp. The simple axially dispersed plug flow model comprising one dimensionless criterion, the Péclet number, was used for displacement washing of black liquor from packed fibre bed using pure wash water with temperature of 10 to 60 °C. The pulp fibre beds were characterised by their hydraulic resistance, average specific resistance, porosity, and equivalent pore diameter, influencing the flow of wash liquid through pulp bed. From breakthrough curves, the wash yield and the Péclet number were evaluated. The results obtained showed that the wash yield is mainly influenced by the Péclet number, characterising the time dependence of alkali lignin removal from the pulp bed, however, the effect of the wash water temperature upon the wash yield was not proved in the given temperature range.
Vytěsňovací praní sulfátové buničiny při různé teplotě prací kapaliny
Keywords: displacement washing; fibre bed resistance; kappa number; kraft pulp; wash yield.; vytěsňovací praní; odpor vrstvy vláken; kappa číslo; sulfátová buničina; výtěžek praní